2017
DOI: 10.1007/s10096-017-3154-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of colonization with Staphylococcus species among patients scheduled for cardiac and orthopedic interventions at tertiary care hospitals in north-eastern Germany—a prevalence screening study

Abstract: As methicillin-resistant Staphylococcus aureus (MRSA) colonization and infection in humans are a global challenge. In Mecklenburg and Western Pomerania (Germany) 1,517 patients who underwent surgical interventions were systematically screened for MRSA and MSSA colonization on the day of hospital admission and discharge. Demographic data, risk factors and colonization status of the (i) nose, (ii) throat, (iii) groin, and (iv) thorax or site of surgical intervention were determined. Of the 1,433 patients who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
0
11
2
Order By: Relevance
“…When examining different surgical categories, we were able to demonstrate that SSI-rates were significantly higher in men undergoing orthopedic and trauma procedures. A prevalence study investigating predictors of colonization with Staphylococcus species in patients undergoing cardiac and orthopedic surgery found significantly higher colonization rates in men [13]. With Staphylococcus aureus being the most common SSI-causing pathogen, it is conceivable that this disparity in colonization patterns could partially explain the gender-related differences in SSI-rates.…”
Section: Discussionmentioning
confidence: 99%
“…When examining different surgical categories, we were able to demonstrate that SSI-rates were significantly higher in men undergoing orthopedic and trauma procedures. A prevalence study investigating predictors of colonization with Staphylococcus species in patients undergoing cardiac and orthopedic surgery found significantly higher colonization rates in men [13]. With Staphylococcus aureus being the most common SSI-causing pathogen, it is conceivable that this disparity in colonization patterns could partially explain the gender-related differences in SSI-rates.…”
Section: Discussionmentioning
confidence: 99%
“…There is a huge difference in the epidemiology of MRSA worldwide. For example, the prevalence of community-associated MRSA infection in Japan, Germany, Turkey, Taiwan, and Malta was found to be 0.94% [29], 1.2% [17], 1.2% [30], 3.8% [31], and 8.81% [6] respectively. These differences can be attributed to variations in microbiological methods (sampling technique, culture sites, and method of MRSA identification), local infection control standards, and the local prevalence of MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…However, obesity did not turn out to be a significant risk factor for MRSA colonization in this study. Neidhart et al [17] reported a reduced risk for S. aureus carriage in obese (BMI ≥ 30.0 kg/m 2 ) compared to overweight patients (BMI of 25.0 to 30 kg/m 2 ). However, other studies reported the opposite result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the prevalence of communityassociated MRSA infection in Japan, Germany, Turkey, Taiwan, and Malta was found to be 0.94%, 1.2%, 1.2%, 1 3.8%, 1 and 8.81% 1 respectively. [8][9][10][11][12] This variation of nasal carriage rate of S. aureus in studies might be due to difference in the characteristics of the study population, quality of sampling, culturing techniques, geographical distribution, and diagnostic techniques. 13 A previous study reported an MRSA colonization rate in diabetics as 10.2%, whereas in another study it was 19% in diabetics on hemodialysis.…”
Section: Discussionmentioning
confidence: 99%